PROBLEMS AND PROSPECTS OF SYSTEM MODERNIZATION OF THE ARCTIC NATURAL GAS EXPORT ON THE EUROPEAN MARKET - V. S. Selin; V. A. Tsukerman (Модернизация, инновация, развитие, 2017)
A research purpose is the analysis of the European natural gas market environment and the modernization opportunities of the delivery system from Russia in connection with the current geo-economic changes. The main methods are the factorial approaches and the content analysis, which allows allocate and structure this sector’s driving forces.Export of the Russian natural gas on the European market still remains the dominating activity, in terms of the total amounts of deliveries, though over the last ten years its specific weight has been considerably reduced. The situation has sharply become aggravated both in connection with the "Ukrainian" crisis, and that of the European Union policy, which is taking the active measures for the gas supply system diversification. As a result of the conducted research it is proved that the Russian gas transportation system in the Arctic regions requires the strategic upgrade which shall go in two main directions.The first direction is the forming of the new pipeline schemes replacing the unreliable transit routes. The second direction is a rather innovative development of exploration and transportation of the liquefied natural gas which amount exceeds thirty percent in world export and in Russian has not yet reached ten percent.Scientific novelty of the received results consists in system approval of the opportunities of adaptation of Russian export deliveries to the market demand changes. The proposals of increase of the liquefied natural gas exploration in the Arctic regions and formation of the basic centers (special zones) have also a practical importance.